Penguatan Keimanan Umat di Kecamatan Manggala Melalui Program KKN STIBA Makassar - Ahmad Syaripudin; Zulfiah Sam (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
Manggala Subdistrict is one of 14 subdistricts in Makassar City. The area of Manggala sub-district is 24.14 km2 or 13.73% of the area of Makassar City. Manggala sub-district consists of 8 villages namely Bontoala, Bangkala, Batua, Borong, Manggala, Tamangapa, Biring Romang and Antang. The purpose of this STIBA Makassar Real Work Lecture (KKN) batch IV is a form of community service which is a pillar of the Tri Dharma of Higher Education. The method of implementing community service programs begins with mapping the problems and needs of the community using SOAR. After the analysis is carried out, a work program that is appropriate and needed by the community is prepared. Work programs that have been successfully implemented include: Socialization and Gathering, Clean Saturdays in Manggala District, Makassar City, Book Review "Ramadankan Your Life", Social Service in Manggala District, Makassar City, Tahsin and Tajwid Teaching Activities, 7 Days Daurah Activities to Memorize Al-Quran Qur'an, Kindergarten/TPA Teaching Activities, and Arabic Halaqah Activities. All of these programs have been running well and have shown initial results in accordance with the KKN objectives that have been proclaimed.